Los principios de la nacionalidad dependiente e independiente de los cónyuges: ventajas y desventajas - Seyyed Mohsen Hashemi-Nasab Zavareh; Elham Ghaffarian; Naser Ghamkhar (Ius Humani. Jornal do direito, 2018)
On marriage issues, many countries have espoused the independence of nationality policy, that is, they accept neutral effects of marriage on nationality. We don’t see the point of bestowing nationality on an alien woman who has married a national man but lives abroad. The ratio of countries in favor of dependent nationality to those in favor of independent nationality is one to three. So, there are only a few countries left still pursuing a policy of forcing husbands’ nationality upon alien women on an unconditional basis. The main question in this paper is: Should the nationality of one spouse be imposed on the other one, making them both subjects of one State? After an introduction (chapter Ⅰ), we analyze the theory of the unity of nationality and the theory of independent nationality (chapter Ⅱ). In chapter Ⅲ we see international documents on the theories of dependent and independent nationality. Finally, we take care of the present situation of the world in respect to nationality laws and then we resume some conclusions; the main one is that some political approaches seems to discriminates between national and foreign women.